2017
DOI: 10.1016/j.chom.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A Large Polysaccharide Produced by Helicobacter hepaticus Induces an Anti-inflammatory Gene Signature in Macrophages

Abstract: SummaryInteractions between the host and its microbiota are of mutual benefit and promote health. Complex molecular pathways underlie this dialog, but the identity of microbe-derived molecules that mediate the mutualistic state remains elusive. Helicobacter hepaticus is a member of the mouse intestinal microbiota that is tolerated by the host. In the absence of an intact IL-10 signaling, H. hepaticus induces an IL-23-driven inflammatory response in the intestine. Here we investigate the interactions between H.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 61 publications
0
75
0
Order By: Relevance
“…IL‐10 is a prototypical anti‐inflammatory cytokine which inhibits the synthesis of pro‐inflammatory cytokines such as TNF‐ɑ and IFN‐Ɣ thus limiting pathological cell shedding responses 30 . IL‐10 induction has previously been described to be driven by certain microbiota members such as Bacteroides , Bifidobacterium and Helicobacter , suggesting that specific members may play a key role for inducing anti‐inflammatory and anti‐apoptotic responses, thereby driving protective barrier integrity during the neonatal period 31-34 …”
Section: Discussionmentioning
confidence: 99%
“…IL‐10 is a prototypical anti‐inflammatory cytokine which inhibits the synthesis of pro‐inflammatory cytokines such as TNF‐ɑ and IFN‐Ɣ thus limiting pathological cell shedding responses 30 . IL‐10 induction has previously been described to be driven by certain microbiota members such as Bacteroides , Bifidobacterium and Helicobacter , suggesting that specific members may play a key role for inducing anti‐inflammatory and anti‐apoptotic responses, thereby driving protective barrier integrity during the neonatal period 31-34 …”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a prototypical anti-inflammatory cytokine which inhibits the synthesis of pro-inflammatory cytokines such as TNF-ɑ and IFN-Ɣ thus limiting pathological cell shedding responses [23]. IL-10 induction has previously been described to be driven by certain microbiota members such as Bacteroides, Bifidobacterium and Helicobacter, suggesting that specific members may play a key role for inducing anti-inflammatory and anti-apoptotic responses, thereby driving protective barrier integrity during the neonatal period [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…ROR γ t + Treg cells specific for Helicobacter hepaticus have also been shown to mediate tolerance to this commensal pathobiont, and a polysaccharide from the same species induces anti‐inflammatory IL‐10 secretion in intestinal macrophages . However, Helicobacter specificity itself does not dictate an anti‐inflammatory programme.…”
Section: Immune Cell–microbiota Crosstalkmentioning
confidence: 99%
“…120 RORct + Treg cells specific for Helicobacter hepaticus have also been shown to mediate tolerance to this commensal pathobiont, 121 and a polysaccharide from the same species induces anti-inflammatory IL-10 secretion in intestinal macrophages. 122 However, Helicobacter specificity itself does not dictate an anti-inflammatory programme. A recent study demonstrated that the same Helicobacter-specific T cells differentiate to Treg cells during homeostasis and effector T cells during colitis.…”
Section: Microbiota Modulation Of Intestinal Lymphocytesmentioning
confidence: 99%